FEATURES OF THE SCHEMES OF CASH PAYMENTS AND BANKING OPERATIONS WITH MONEY LAUNDERING - Irina N. Mihailova (Статистика и экономика)
The scientific article is devoted to problems of identification schemes origin of the property and money by making a wide range of transactions and financial operations in business and other economic activity, which is carried out by change of the nominal owner of the property (front companies). In most cases, these transactions have no economic sense. For the legislation of criminal possession of property transactions are documented. In the process of legalization of income obtained illegally are in the form of goods, funds, securities, property rights, which require constant perfection of methods for the detection of fraudulent schemes.